PERAN RASIO NEUTROFIL – LIMFOSIT PRA BEDAH SEBAGAI PREDIKTOR NYERI PADA PASIEN YANG MENJALANI OPERASI DEKOMPRESI DAN STABILISASI POSTERIOR (TINJAUAN TERHADAP INTENSITAS NYERI) - Rahim, Octaviana Indri Sakti; Ratnawati, .; Ala Husain, Alamsyah Ambo; Ahmad, Muh. Ramli; Wirawan, Nur Surya; Wijaya Tan, Charles (E-Jurnal Medika Udayana, 2024)
Background: Posterior decompression and stabilization on the vertebrae is a surgical procedure performed to treat the main cause of low back pain. NLR perioperative examination is very rarely used in determining the level of postoperative pain and can help in planning of postoperative analgesic drugs, even though this examination is certainly available as a perioperative assessment. Purpose: This study aims to assess the relationship between NLR preoperative as a predictor of pain with pain intensity and IL-6 levels postoperative in patients undergoing posterior decompression and stabilization surgery. Methods: This research is an analytical observational study with a prospective cohort design, which was carried out at Wahidin Sudirohusodo Hospital. The sample for this study was all patients who underwent elective surgical procedures for Decompression and Posterior Stabilization of the Lumbar Region at Dr. RSUP. Wahidin Sudirohusodo Makassar with 30 samples. Results: There was a strong, significant correlation between the average NRS at rest and the NLR group, as well as the average NRS with movement, p value < 0.05, r > 0.7. In IL-6 postoperative and delta-IL-6 levels, there was a statistically significant difference in IL-6 levels between the two groups with a p value <0.05. There is a significant difference in the need for the opioid Fentanyl in the two groups with a p value <0.05. Conclusion: There was an increase in the pain intensity and IL-6 levels postoperative, as well as an increase in total opioids consumptions in patients undergoing decompression and posterior stabilization of the lumbar region with NLR preoperative ? 2 compared to NLR < 2. NLR can be used as a predictor of postoperative pain which is good, therefore it can be used as a reference for appropriate postoperative pain management. Keywords: posterior decompression and stabilization, pain intensity, interleukin-6, numeric rating scale, neutrophil lymphocyte ratio